Implementasi Video Motion Graphic Penggunaan Aplikasi Ujian CBT Terhadap Pemahaman Siswa Dengan EPIC Model - Elvyna Nur Azizah Wisnu Wardani (Politeknik Negeri Batam, 2022)
Submission of information at Batam State vocational high school 3 uses conventional methods which in the era of the industrial revolution 4.0 were less desirable. So we need a model for delivering information that is more attractive and easily understood by the audience, one of them is motion graphics. Based on these conditions, it is necessary to create or design a Motion graphic video which is an alternative as a medium for distributing information that is interesting and adapted to the character of students during the era of the industrial revolution 4.0. Based on the research that has been done, the results obtained from 4 aspects of the EPIC Model with an empathy value of 4.2, persuation value of 3.9, impact value of 4.13, and the value of communication is 4.33. after that look for the value of the EPIC Rate of the four values ​​and get the value of the EPIC Rate of 4.15 with effective category. From the data that has been obtained, it can be concluded that This video on how to use the Beesmart CBT application is effectively used as a media to provide information on how to use the Beesmart CBT exam application for students of atam State vocational high school 3.